A indústria 4.0 e a formação do engenheiro civil: a influência da empresa júnior como catalisadora de conhecimento - COSTA, Jonathas Miranda da (2023)
The Junior Company (JC) as a non-profit company, is able to offer its member students qualifications and experience as a complement to the acquired knowledge in the classroom. Therefore, an important factor in the training of civil engineer in the face of 4.0 industry, considered by some scholars as the fourth industrial revolution. The industry is characterized by the decentralized control of production processes that bring the physical and biological worlds closer to the digital world. This study aimed to analyze which would be the necessary skills and competences for the civil engineer required by current job market and how the Junior Company can help in the learning of these skills and competences. As a methodology, three questionnaires were prepared, aimed at civil engineering students who passed through the JC, those who did not pass through the JC and for qualified civil engineering professionals. The results obtained showed that JC has great relevance in preparing for the job market, especially related to management and entrepreneurship. The skills and competencies required by the current job market were identified, and the importance of knowledge in civil engineering software such as Excel, budget software and Revit was analyzed.